LncRNA USP2-AS1 Promotes Hepatocellular Carcinoma Growth by Enhancing YBX1-Mediated HIF1α Protein Translation Under Hypoxia - Chen, Shi-Ping; Zhu, Gui-Qi; Xing, Xiao-Xia; Wan, Jing-Lei; Cai, Jia-Liang; Du, Jun-Xian; Song, Li-Na; Dai, Zhi; Zhou, Jian (Frontiers in Oncology, 2022)
Recently, the role of lncRNAs in tumorigenesis and development has received increasing attention, but the mechanism underlying lncRNAs-mediated tumor growth in the hypoxic microenvironment of solid tumors remains obscure. Using RNA sequencing, 25 hypoxia-related lncRNAs were found to be upregulated in HCC, of which lncRNA USP2-AS1 were significantly increased under hypoxia. We further confirmed that USP2-AS1 was significantly upregulated in liver cancer using FISH assay and that USP2-AS1 was associated with advanced liver cancer and increased tumor size. Furthermore, overexpression of USP2-AS1 under hypoxia dramatically increased HCC proliferation and clone formation, whereas the opposite results were observed after USP2-AS1 knockdown. We also found that overexpression of USP2-AS1 increased migration and invasion of HCC cells，while USP2-AS1 knockdown led to the opposite effect. In addition, USP2-AS1 knockdown can increase the efficacy of lenvatinib in our mice tumor xenograft model. Our findings also suggest that USP2-AS1 could increase the protein level of HIF1α by enhancing YBX1 protein binding to HIF1α mRNA under hypoxia and the therapeutic effect of lenvatinib can be enhanced by combination with HIF1α inhibitors in liver cancer.